The Social Structure of the First Crusade - Kostick, Conor (The Medieval Mediterranean, 2008)
This books provides a detailed analysis of the social structure of the First Crusade (1096 - 1099) along with an original assessment of the sociology of its contemporary or near contemporary sources.